1996
DOI: 10.1021/ic951382q
|View full text |Cite
|
Sign up to set email alerts
|

A Genuine Example of a Discrete Bimetallic (Cu, Gd) Complex:  Structural Determination and Magnetic Properties

Abstract: The LCuGd(NO3)3·Me2CO complex crystallizes in the monoclinic space group P21/c (No. 14) in a cell having the dimensions a = 9.799(1) Å, b = 18.926(3) Å, c = 16.012(1) Å, β = 96.530(8)°, Z = 4. The four units forming the unit cell do not display any obvious short contacts between them. The magnetic behavior is characteristic of a ferromagnetic interaction between the Gd3+ and Cu2+ ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
284
1
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 308 publications
(317 citation statements)
references
References 9 publications
(21 reference statements)
21
284
1
3
Order By: Relevance
“…Bridging O2 and O2 i atoms simultaneously occupy both inplane and apical coordination sites of copper(II) nuclei within dimeric unit. The apical bond of bridging atom is as expected 0.49 Å longer (Cu1-O2i bond is 2.447 Å and Cu1-O2 bond is 1.960 Å) than the basal plane distance and is shorter than these in formerly studied five analogous structures [24,[25][26][27][28]. The other in-plane bond distances are quantitatively comparable with corresponding values.…”
Section: Results and Disccussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Bridging O2 and O2 i atoms simultaneously occupy both inplane and apical coordination sites of copper(II) nuclei within dimeric unit. The apical bond of bridging atom is as expected 0.49 Å longer (Cu1-O2i bond is 2.447 Å and Cu1-O2 bond is 1.960 Å) than the basal plane distance and is shorter than these in formerly studied five analogous structures [24,[25][26][27][28]. The other in-plane bond distances are quantitatively comparable with corresponding values.…”
Section: Results and Disccussionsupporting
confidence: 84%
“…In the most cases where tridentate N 2 O Schiff base ligands are incorporated, square-pyramidal one-atom bridged complexes of type b are mainly obtained [24][25][26][27][28][29][30] and in this array, Schiff base ligands resides in basal plane while one bridging atom occupies the axial position of one monomeric unit and the other locates in basal plane of the same unit. This type of dimers display weak exchange coupling, often antiferromagnetic, as expected since only one atom participates bridging mode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3, 5 These pure heterodimetallic systems open new perspectives for (i) the exploration of interactions between f-and d-block ions possessing first-order orbital momenta, [5][6][7][8] (ii) the preparation of extended and organised heterotrimetallic d-fd 14 and f-d-f 15 architectures in the solid state and (iii) the detailed re-examination of the intimate mechanism proposed by Goodenough.…”
Section: -58mentioning
confidence: 99%
“…[3] However, Costes et al have reported the synthesis of an antiferromagnetically coupled Gd(III)-Cu(II) dinuclear complex in which Gd(III) and Cu(II) are unsymmetrically bridged by a phenolate O and an oximato (N-O) group. [4] The reactions described in this work are part of an effort to expand the type of bridging ligand used to link Gd(III) and Cu (II). In previous work we demonstrated the effectiveness of Cu(2,2-oxomac) [5] and Cu(3,2-oxomac) [6] (see figure 1) as dinucleating ligands by the preparation of adducts between these complexes and M(hfa) 2 (M = Cu or Ni) in which two oxamide oxygen atoms on adjacent carbon atoms of the macrocycles serve as linkages between Cu(II) and M (II).…”
mentioning
confidence: 99%